Gender Variation of Paracentral Lobule Among Bangladeshi Population: A Cross-Sectional Study - Chowdhury, Mahfuza; Khatun, Monira; Ahmed, Rukshana; Afrin, Tamanna; Shahin, Rebeka; Tripti, Durratul Jannat (Bangladesh Journal of Anatomy, 2018)
Background: The paracentral lobule is the area on medial surface of the cerebral cortex surrounds the indentation produced by the upper end of central sulcus on the superior border. Any trauma, tumor, or cerebral ischemia cause lesions of motor and sensory cortex of paracentral lobule. This study was carried out to observe the morphometric pattern of paracentral lobule in adult male and female Bangladeshi population for establishment of a baseline anatomical normative data of our own for future studies. Materials and Methods: This cross- sectional study was conducted in the Department of Anatomy, Dhaka Medical College, Dhaka, during the period of January 2017 to December 2017. A total of 70 adult Bangladeshi (35 male and 35 female) age ranging from 20-65 yrs were selected. CT scan image of brain in mid sagittal view was used for this study. Data were analyzed by Unpaired Student’s ‘t’ test. Results: The length of motor and sensory area and width of motor area of right and left paracentral lobule was significantly higher in male. Non-significant difference was found in width of sensory area between male and female. Conclusion: The present study reveals significant difference in morphological measurements of right and left paracentral lobule between male and female of adult Bangladeshi population. Bangladesh Journal of Anatomy July 2018, Vol. 16, No. 2, pp. 46-50